AI Paradox: Investigating Behavioral Divergence and Cognitive Offloading in AI-Assisted English Language Teaching for SMTP Students - Boonchat Mekkaeo; Parkpoom Sungchuay; Supawadee Thibai (PT. Academic Bright Collaboration, 2026)
Purpose – This study investigates the